2006
DOI: 10.1103/physrevb.73.100408
|View full text |Cite
|
Sign up to set email alerts
|

Percolative transition on ferromagnetic insulator manganites: Uncorrelated to correlated polaron clusters

Abstract: We report an atomic-scale study on the ferromagnetic insulator manganite LaMnO 3.12 using ␥-␥ perturbed angular correlation spectroscopy. Data analysis reveals a nanoscopic transition from an undistorted to a JahnTeller ͑JT͒ distorted local environment upon cooling. The percolation thresholds of the two local environments enclose a macroscopic structural transition ͑rhombohedral-orthorhombic͒. Two distinct regimes of JT distortions were found: a high-temperature regime where uncorrelated polaron clusters with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…For all compositions the system presents an orthorhombic distorted perovskite structure and CO is stabilized over a broad range of compositions, with x extending from 0.30 to 0.90, in good agreement with the literature [16 -18]. Using the 111m Cd -perturbed angular correlation technique (PAC) [19] the measurement of the EFG tensor at the Ca= Pr site was performed in a series of samples ranging from x 0-1, in the 10 -1000 K temperature range (for typical experimental details see [15]). The samples under study were implanted at ISOLDE/CERN with 111m Cd to a dose lower than 1 ppm of the Pr =Ca concentration.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…For all compositions the system presents an orthorhombic distorted perovskite structure and CO is stabilized over a broad range of compositions, with x extending from 0.30 to 0.90, in good agreement with the literature [16 -18]. Using the 111m Cd -perturbed angular correlation technique (PAC) [19] the measurement of the EFG tensor at the Ca= Pr site was performed in a series of samples ranging from x 0-1, in the 10 -1000 K temperature range (for typical experimental details see [15]). The samples under study were implanted at ISOLDE/CERN with 111m Cd to a dose lower than 1 ppm of the Pr =Ca concentration.…”
supporting
confidence: 60%
“…This is connected to the relatively high conductivity of these materials, and to the possibility that the suspected electric dipole order may only occur within nanoscopic regions. However, a very recent work of Jooss et al [13] provides, by refinements of electron diffraction microscopy data, indirect evidence for canted antiferroelectricity in Pr 0:68 Ca 0:32 MnO 3 .The measurement of the electric field gradient tensor (EFG) via hyperfine techniques offers a very sensitive tool to locally study phase transitions and probe electric ordering [14,15]. Aiming to get further insight on the microscopic nature of CO we performed a detailed study on the EFG temperature trends across the Pr 1ÿx Ca x MnO 3 phase diagram.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on XRD and magnetic measurements, also performed after the PAC experiments, the high quality of the samples show that the origin of this EFG b also cannot be attributed to impurities. Thus the origin of the higher V zzb local environment is not clear and do not seem related to the quality of the samples nor defects created by the implantation process since previous studies showed that the present annealing was sufficient to recover from implantation defects [15,16]. The existence of this second EFG distribution seems to be intrinsic to this system and has to be found in more subtle grounds.…”
Section: Resultsmentioning
confidence: 88%
“…The EFG principal component, V zz , shows the typical decrease on its magnitude with increasing temperature for both EFG a and EFG b . This trend was found in perovskite systems [15,16] and is frequently associated to an increase of the atomic vibrations due to the increase of temperature. The asymmetry parameter, η, is also constant with temperature, with small variations within the error bars for both EFG distributions.…”
Section: Resultsmentioning
confidence: 94%